Management of wilt and root rots of chickpea (Cicer arietinum) using Trichoderma harzianum in India - DUBEY, S C; SINGH, BIRENDRA; GUPTA, O M; SAXENA, D R; SHARMA, O P; KOHIRE, O D; ANADANI, V P; SINGH, R K; SINGH, S K; TRIPATHI, ARADHIKA (The Indian Journal of Agricultural Sciences, 2017)
Wilt (Fusarium oxysporum f. sp. ciceris), dry root rot (Rhizoctonia bataticola) and collar rot (Sclerotium rolfsii) are the major soil-borne diseases of chickpea (Cicer arietinum) prevalent across the country and causing substantial yield losses. Field experiments were conducted at eight different hot spot locations of these diseases belonging to six states namely, New Delhi (Delhi), Indore, Sehore and Jabalpur (Madhya Pradesh), Badnapur (Maharashtra), Junagadh (Gujarat), Samba (Jammu and Kashmir) and Durgapura (Rajasthan) to evaluate and validate the performance of Pusa 5SD (a novel seed dressing formulation developed from Trichoderma harzianum) alone and in combination with fungicide along with recommended fungicidal seed treatment against wilt and root rots of chickpea under AICRP Chickpea during 2010 to 2013 crop seasons. Seed treatment with Pusa 5SD (T. harzianum) alone and in combination with Vitavax power (carboxin + thiram) proved to be effective for the management of wilt and root rots at different locations. A combination of seed treatment with Pusa 5SD and Vitavax power (carboxin + thiram) provided the lowest disease incidence (12.2%) along with the highest grain yield (1053.3 kg/ha). Cardendazim (Bavistin) + Tetra methyl thiuram disulphide (thiram) and Vitavax power also reduced the diseases incidence (13.0%) and enhanced the grain yield (998.2 kg/ha) of chickpea. The bio-formulation Pusa 5SD showed effectiveness across the locations and varieties against wilt, dry root rot and collar rot of chickpea.